KAJIAN USAHATANI TUMPANG GILIR TANAMAN PADI DAN TOMAT DI DESA WOLAANG KECAMATAN LANGOWAN TIMUR - Marisa Solar; Celsius Talumingan; Esry O.H. Laoh; Martha M. Sendow (Universitas Sam Ratulangi, 2015)
ABSTRACT Rotate overlap is a system of farming for a year or more consisting of several times planting one or several types of crops in rotation . This study aims to determine the magnitude of Rice and Tomato farm income as a plant overlapping shifts during one year . There are many combinations of plants that are cultivated farmers within one year of production , and kombinassi - combination of these plants generally always be replaced in each year . Production depends on weather conditions and market demand . The benefits of this research as information for researchers , and as fill material for the extension agencies concerned and the parties need .